T2* MRI of minimal hepatic encephalopathy and cognitive correlates in vivo. Issue 1 (25th September 2012) - Liu, Jian‐Ying; Ding, Jing; Lin, Dong; He, Yi‐Feng; Dai, Zhi; Chen, Cai‐Zhong; Cheng, Wei‐Zhong; Wang, He; Zhou, Jian; Wang, Xin
Abstract Purpose: To evaluate regional brain iron deposition in minimal hepatic encephalopathy (MHE) patients using T2*‐weighted gradient‐echo imaging and to explore the relationship between T2* MR changes and cognitive performance. Materials and Methods: Forty hepatitis‐B virus (HBV)‐related cirrhotic patients and 22 age‐, sex‐, and education‐matched healthy controls were included in this study. Of the patients, twenty eight patients were diagnosed with MHE. All subjects were administered Number Connection Test‐A (NCT‐A), Letter Digit Substitution Test (LDST), Rey‐Osterrieth Complex Figure Test (RCFT), and the Mini‐Mental State Examination (MMSE). T2*‐weighted gradient‐echo images were acquired using 3 Tesla MRI. Phase values (putative iron levels) in the frontal–basal ganglia–thalamocortical circuits were measured. Spearman correlation and multiple linear regression analysis were performed. Results: MHE patients exhibited significantly prolonged NCT‐A time and decreased LDST, RCFT immediate and delayed recall scores. Significant decreases of phase values in the bilateral putamen were detected in MHE patients compared to without MHE patients and controls. Multiple linear regression analysis confirmed significant correlations between the phase values in the putamen and right frontal white matter and cognitive performances by MHE patients. Conclusion: Decreased phase values in the frontal cortical–basal ganglial circuits independently contribute to cognitive impairments in MHE patients. J. Magn. Reson. Imaging 2013;37:179–186. © 2012 Wiley Periodicals, Inc.